Pengembangan Model Teaching Factory di Bengkel Otomotif SMK Karsa Mulya Palangka Raya - Galfri Siswandi; Sukoco Sukoco (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
The objective of the study is to develop an applicable Teaching factory model for practices in the automotive workshop of SMK Karsa Mulya Palangkaraya. This study used a quantitative approach. It was conducted in grade XI of Motorcycles Engineering Department at SMK Karsa Mulya Palangkaraya. It was carried out in five phases: (1) preliminary investigation, (2) design; (3) realization / construction, (4) test, evaluation and revision, (5) field testing / implementation. Data collection instruments consisted of observation sheets and assessment sheets. The results of the competency tests of 19 students were: (a) Tune Up; the highest score, the lowest score and the average score were 98.82, 89.41, 95.23 respectively (b) Over Haul; the highest score, the lowest score and the average score were 90.67, 82.67, 85.55 respectively (c) System Starter; the highest score, the lowest score and the average score were 80.00, 77.33, 78.00 respectively. Thus it was noted that the model can be applied in the vocational workshop of Motorcycle Engineering Department at SMK Karsa Mulya Palangkaraya